Geopolitics and expertise : knowledge and authority in European diplomacy - Kuus, Merje (Chichester : Wiley, 2013)
Geopolitics and Expertise is an in-depth exploration of how expert knowledge is created and exercised in the external relations machinery of the European Union. Provides a rare, full-length work on transnational diplomatic practice. Based on a rigorous and empirical study, involving over 100 interviews with policy professionals over seven years. Focuses on the qualitative and contextual, rather than the quantitative and uniform. Moves beyond traditional political science to blend human geography, international relations, anthropology, and sociology.
Cosmopolitan Brussels"Natural reflex"; "In the third degree of depth"; "An urbane, subtle approach"; The big unsaid: money; La bella figura; Learning ease; Shifts and Spirals; Notes; Chapter Seven Political Geographies of Expertise; Knowledge From and On the East; Finding a Market; Learning and teaching; "Things are evolving"; Adaptation; The uses of history; Managing Difference; Notes; Conclusion: Circles of Knowledge; Spaces and Agents of Bureaucratic Knowledge; Less is More; Notes.
Includes bibliographical references and index.
Print version record.
Keywords: Geopolitics -- Europe; Diplomacy -- History -- 20th century; Diplomacy -- History -- 21st century; Geopolitics -- 20th century; Geopolitics -- 21st century; Diplomatic relations; Geopolitics; European Union countries -- Foreign relations; Europe; Europe -- European Union countries; Electronic books